Rancangan Aplikasi Pemesanan Makanan dan Minuman di Mona Cafe Berbasis Desktop dalam Pemrograman Berbasis Objek dengan Menggunakan Netbeans - Aulia Kartika Dewi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Technological advancements encourage the culinary business sector to adopt digital systems to improve operational efficiency. One such innovation is a desktop-based food ordering application. Mona Cafe in Medan developed this system to make it easier for customers to place orders without waiting long or writing them down manually. This application allows customers to select menus digitally, making the ordering process more practical and efficient. Additionally, it helps waiters record and manage orders more systematically, reducing errors and speeding up service. This technology also aligns with the digitalization trend, especially in attracting millennials and Gen Z. Besides enhancing customer convenience, this application helps Mona Cafe stay competitive in the growing culinary business. Developed using the waterfall method, the system makes cafe operations more structured and professional. With this innovation, Mona Cafe is expected to improve its service quality and customer satisfaction